PENGARUH PEMBERIAN ASI EKSKLUSIF TERHADAP TUMBUH KEMBANG BAYI UMUR 6-24 BULAN DI NAGARI SARIAK LAWEH KEC. AKABILURU - Mukhlis, Hendra (Sainstek : Jurnal Sains dan Teknologi, 2019)
Infant growth is largely determined by the amount of breast milk obtained including the energy and other nutrients contained in breast milk. Breastfeeding in Indonesia has decreased, especially in West Sumatra based on Indonesia Health Profile in 2014. This study aims to determine the Influence of Exclusive Breastfeeding on the growth and development of infants aged 6-24 months in Nagari Sariak Laweh Working Area Batu Hampar Puskesmas, District Akabiluru. The measured growth consists of body weight, body length and Head Circumference. Progress was seen through KPSP (Pre-Growth Questionnaire Developments). This type of research is an observational research that is analytic with Cross-Sectional research design. Data analysis used was univariate and bivariate (Independent T test). The study period was from October 2017-February 2018. The population in the study were infants aged 6-24 months in Nagari Sariak Laweh. The sample in this study amounted to 30 babies. Data collection was done by using questionnaire and direct measurement. The statistical results show that there is no Influence of Exclusive Breastfeeding on Infant Growth (body weight, body length, head circumference) and no Influence of Exclusive Breast Feeding on Infant Development (based on KPSP questionnaire).